Investigations on AWJ cutting process of hybrid aluminium 7075 metal matrix composites using nozzle oscillation technique. (2020) - Nandakumar, N.S.; Sasikumar, K.S.K.; Sambathkumar, M.; Saravanan, N.
Abstract: Difficult-to-machine materials like composites, super alloys and ceramics are cut by Abrasive water jet cutting (AWJC). However, the failure of the jet to cut through the work piece is a major issue particularly in thicker materials. The jet's inability to produce longer smooth cut surface, minimum surface roughness and minimum kerf taper are the major challenges the researchers are trying to find solutions. This paper addresses the three issues in cutting of aluminum 7075 hybrid metal matrix composites. The hybrid composite is developed by incorporating two reinforcements (B4 C and TiC) into Aluminum matrix. Cutting experiments were carried out on Pure AL7075, AL7075 + (2.5%B4C + 2.5%TiC), AL7075 + (5%B4C + 5%TiC)AL7075 + (7.5%B4C + 7.5%TiC). The surface generated, smooth cut region and kerf taper were analyzed on the all composite machined using AWJC machine.